Ontology engineering in virtual breeding environments - Simões, Dora (2012)
This paper proposes a new method for managing the use of ontologies in the context of a Virtual Breeding Environment. This research work focus is on the dissolution phase of a Virtual Enterprise or Collaborative Network, whereontology segmentation techniques are user to enrich the VBE's ontology library. Firstly, an overview of the process of ontology composition and decomposition is given and the ontology library system adopted described.Then, the ontologies' ranking and classification method is described,explaining a set of metrics inspired in social network approaches. Finally, the results of preliminary tests are discussed.